24.96%‐Efficiency FACsPbI3 Perovskite Solar Cells Enabled by an Asymmetric 1, 3‐Thiazole‐2, 4‐Diammonium. Issue 15 (1st March 2023) - Zhou, Hui; Yang, Lu; Duan, Yuwei; Wu, Meizi; Li, Yong; Xu, Dongfang; Zou, Hong; Wang, Jungang; Yang, Shaomin; Liu, Zhike
Abstract: Surmounting complicated defects at the electron transport layer (ETL) and perovskite interface plays a non‐trivial role in improving efficiency and stability of perovskite solar cells (PSCs). Herein, an asymmetric interface modification strategy (AIMS) is developed to passivate the defects from both a SnO2 ETL and the perovskite buried surface via incorporating 1, 3‐thiazole‐2, 4‐diammonium (TDA) into the SnO2 /perovskite interface. Detailed experimental and calculated results demonstrate that N3 (the nitrogen atom bonding to the imine) in the TDA preferentially cures the free hydroxyl (OH), oxygen vacancy ( V O ), and the Sn‐related defects on the SnO2 surface, while N1 (the nitrogen atom bonding to the vinyl) is more inclined to passivate the Pb 2+ and I − related defects at the perovskite buried surface. As a result, the TDA‐modified FACsPbI3 PSC yields a champion power conversion efficiency (PCE) of 24.96% with a gratifying open‐circuit voltage ( V oc ) of 1.20 V. In addition, the optimized PSCs exhibit charming air‐operational stability with the unencapsulated device sustaining 97.04% of its initial PCE after storage in air conditions for 1400 h. The encapsulated device maintains 90.21% of its initial PCE after maximum power point tracking for 500 h. Abstract : Herein, an asymmetric modification strategy is developed by incorporating a thiazole derivative, 1, 3‐thiazole‐2, 4‐diammonium (TDA), into a perovskite/SnO2 interface for high performance FACsPbI3 perovskite solar cells (PSCs). N3 cures the free OH defects on the SnO2 surface, while N1 passivates the Pb 2+ /I − defects from the perovskite‐buried interface. Consequently, the TDA‐modified device achieves nearly 25% efficiency with a high V oc of 1.20 V.